2018
DOI: 10.1016/j.ijplas.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel constitutive model for multi-step stress relaxation ageing of a pre-strained 7xxx series alloy

Abstract: A novel set of unified constitutive equations has been developed and validated to describe stress relaxation ageing (SRA) behaviour. The model, based on dynamic ageing and power-law creep relations, can predict the stress relaxation, age hardening response and their interactions at different temperatures, through considering the microstructure evolutions (precipitate radius, volume fraction and dislocation density) during SRA. In addition, the model newly incorporates the effects of prior cold work. This model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 54 publications
(147 reference statements)
0
18
0
Order By: Relevance
“…Therefore, the yield strength in this state is slightly lower than initial state. Ma et al and Zheng et al [13,14] also demonstrated that the coarsening of the precipitates can be accelerated under higher stress. The comparison of Figure 6b,e shows that the average diameter of the η -precipitate after stress relaxation aging of 6% pre-strain is about 20 nm.…”
Section: Aging Behavior Of Aa7150 Under Different Temperatures Initimentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, the yield strength in this state is slightly lower than initial state. Ma et al and Zheng et al [13,14] also demonstrated that the coarsening of the precipitates can be accelerated under higher stress. The comparison of Figure 6b,e shows that the average diameter of the η -precipitate after stress relaxation aging of 6% pre-strain is about 20 nm.…”
Section: Aging Behavior Of Aa7150 Under Different Temperatures Initimentioning
confidence: 96%
“…σ is the initial stress. Equation (14) indicates that the decrease of stress relaxation rate is due to the slowdown of strain rate. E(T) represents the change of Young's modulus with temperatures within experimental temperature.…”
Section: Constitutive Modeling and The Determination Of Materials Paramentioning
confidence: 99%
See 2 more Smart Citations
“…Due to too many material constants needed to compute in the current constitutive equation, it is difficult to properly fit creep curves using the gradient-based optimization algorithm. With the above creep experiment data for studied 7055-T6 alloy, an advanced algorithm [27], i.e., Genetic Algorithm Optimization Toolbox (GAOT), is employed on MATLAB (Matlab2016a, MathWorks, Inc., Natick, MA, USA) platform to obtain exact constants that can describe the feature of creep and effect of pre-stretching on material, as listed in Table 2. Figure 9 shows the results between fitting predicted curves and experiment data.…”
Section: Determination Of Materials Constants For 7055-t6 Alloymentioning
confidence: 99%